Mutation of Growth Arrest Specific 8 Reveals a Role in Motile Cilia Function and Human Disease. - Wesley R Lewis; Erik B Malarkey; Douglas Tritschler; Raqual Bower; Raymond C Pasek; Jonathan D Porath; Susan E Birket; Sophie Saunier; Corinne Antignac; Michael R Knowles; Margaret W Leigh; Maimoona A Zariwala; et al. (PLoS Genetics, 2016)
Ciliopathies are genetic disorders arising from dysfunction of microtubule-based cellular appendages called cilia. Different cilia types possess distinct stereotypic microtubule doublet arrangements with non-motile or 'primary' cilia having a 9+0 and motile cilia have a 9+2 array of microtubule doublets. Primary cilia are critical sensory and signaling centers needed for normal mammalian development. Defects in their structure/function result in a spectrum of clinical and developmental pathologies including abnormal neural tube and limb patterning. Altered patterning phenotypes in the limb and neural tube are due to perturbations in the hedgehog (Hh) signaling pathway. Motile cilia are important in fluid movement and defects in motility result in chronic respiratory infections, altered left-right asymmetry, and infertility. These features are the hallmarks of Primary Ciliary Dyskinesia (PCD, OMIM 244400). While mutations in several genes are associated with PCD in patients and animal models, the genetic lesion in many cases is unknown. We assessed the in vivo functions of Growth Arrest Specific 8 (GAS8). GAS8 shares strong sequence similarity with the Chlamydomonas Nexin-Dynein Regulatory Complex (NDRC) protein 4 (DRC4) where it is needed for proper flagella motility. In mammalian cells, the GAS8 protein localizes not only to the microtubule axoneme of motile cilia, but also to the base of non-motile cilia. Gas8 was recently implicated in the Hh signaling pathway as a regulator of Smoothened trafficking into the cilium. Here, we generate the first mouse with a Gas8 mutation and show that it causes severe PCD phenotypes; however, there were no overt Hh pathway phenotypes. In addition, we identified two human patients with missense variants in Gas8. Rescue experiments in Chlamydomonas revealed a subtle defect in swim velocity compared to controls. Further experiments using CRISPR/Cas9 homology driven repair (HDR) to generate one of these human missense variants in mice demonstrated that this allele is likely pathogenic.